Exercise Method for Prevention and Treatment of Hypertension in Cipta Harja Village, Cipatat District, Bandung - Ade Ajeng Rahmawati; Julia Annisa Cahayani; Tegar Saputra Yasa (Indonesian Journal of Community Development, 2022)
High blood pressure can worsen a person's quality of life, even hypertension is the cause of other diseases. Prevention is important to prevent and even reduce the risk factors for hypertension. Prevention can be done in various ways, one of which is physical activity. This study aims to determine the management of physical exercise techniques to reduce blood pressure in residents of Cipta Raharja with hypertension. The method used is One Group Pretest-Posttest Design, involving 45 groups of adults to elderly people with hypertension in Cipta Harga Village, Cipatat District. The sampling technique used is accidental sampling. The results showed that hypertension exercise reduced blood pressure in the systolic range of 4 to 34 mmHg and the diastolic range of 5 to 30 mmHg. Measurements were taken before and after hypertension exercise with a rest break after exercise to 1-hour measurement. It can be concluded that hypertension exercise can be used as an intervention option for reducing hypertension.